Розробка інформаційної системи обслуговування глядачів мережі кінотеатрів - Ібрагімлі, Г. (ХНУРЕ, 2023)
This work is devoted to the creation of a corporate web server for a network of cinemas, which allows automating the process of buying and booking tickets by customers. The stages of development, principles and advantages are considered. The result of the work is the developed web server itself, including the user interface, the technical functional basis and the developed database